Combination Therapy of Chronic Endometritis in Women with Infertility and Miscarriage - Kurbaniyazova Aziza Zafarjonovna (Journal of Science in Medicine and Life, 2024)
The problem of chronic endometritis (CE) is very relevant nowadays, because in recent years the frequency of this disease, which has taken an important place in the composition of inflammatory diseases of the genital organs, is increasing. This is partly due to the widespread use of various intrauterine manipulations, abortions, IUDs, etc., which are risk factors for this pathology [41, 97, 118]. CE is of not only medical but also social importance because it often causes reproductive dysfunction, infertility, failed IVF attempts, miscarriage (NP), complicated pregnancy and delivery [26, 27, 84, 168].